New public management and management by results: a bibliometric review of studies in the context of higher education institutions - Guedes, Marcela Boldrini Gazzani; Oliveira, Fabrícia Benda de; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2025)
This article presents a bibliometric review of the implementation and development of New Public Management (NPM) and Results-Based Management in higher education institutions. Aiming to identify research trends and gaps from 2014 to 2024, the review covered publications indexed in the Scopus and Web of Science databases, resulting in 35 selected articles. Quantitative results indicate peaks in publications in the years 2016, 2018, and 2021, with a notable concentration of studies from Australia, the United Kingdom, and the United States. The keyword analysis reveals that the studies predominantly address topics related to performance, accountability, and public sector reforms. Qualitative results show that the articles mainly examine the impacts of Results-Based Management on university funding and faculty performance evaluation, with a focus on structural changes and pressures on academic staff. This study contributes to the understanding of the impacts of NPM and Results-Based Management theories on higher education institutions, identifying a gap in the scientific literature on this topic in Latin American countries. The study suggests the need for further research on the effects of these approaches beyond funding, particularly on the professional lives of faculty members.